PENERAPAN APLIKASI MANAJEMEN LABORATORIUM PADA DINAS PERTANIAN DAN PERIKANAN KOTA BANJARMASIN - Wiranata, Ade Davy; Rachman, Hafid Sulistyo; Saifudin, Yazid (ISTEK WIDURI, 2020)
The Banjarmasin City Agriculture and Fisheries Office in providing innovation desperately needs a management that can manage an organization to be more structured with the specified procedures. The problem in this study is that there is no application program for processing data. The purpose of this research is to create and implement management applications that can help facilitate and accelerate the management of laboratory data at the Banjarmasin City Agriculture and Fisheries Office. The data collection methods used are interviews, observations, and review literature while the research methods used use SDLC waterfall. The result of this research is that the application that has been created can be used to facilitate and speed up the processing of data at the Office of Agriculture and Fisheries Banjarmasin City.